Penggunaan Aplikasi SALAM Dalam Pembelajaran Pendidikan Agama Islam dan Budi Pekerti Kelas VIII di SMP Negeri 1 Sirampog Brebes - Aulia Rizki, Firda; Sumiarti (Jurnal Pendidikan Agama Islam, 2025)
This study aims to analyze the use of the SALAM Application in the learning of Islamic Education and Character Education in grade VIII at SMP Negeri 1 Sirampog Brebes. The SALAM Application, which stands for Islamic Education Learning Application System, is designed to facilitate students in accessing learning materials flexibly and interactively. This research employs a qualitative approach with a descriptive method, involving observation, interviews, and documentation to collect data. The findings indicate that the SALAM Application has a positive impact on the learning process. This application provides various features, including text materials, instructional videos, evaluations, and reflections, which support diverse learning styles among students. Additionally, the use of this application also enhances students’ motivation to learn and makes it easier for teachers to deliver content. However, this study also identifies several challenges, such as limited access to devices and unstable internet connections, which can affect the effectiveness of using the SALAM Application. Nevertheless, the SALAM Application proves to be an innovative and relevant learning medium that meets the educational needs in the digital era. Therefore, this study recommends that teachers continue to utilize the SALAM Application as a teaching aid while providing guidance to students who are not yet accustomed to using technology. This research is expected to serve as a reference for the development of similar applications in other educational fields and contribute to the improvement of the quality of Islamic Education learning in secondary schools.